MLA 15-93 - Mineral Resource Investigation Of The Caribou City-Stump Creek Study Area, Bonneville And Caribou Counties, Idaho - Richard L. Rains (The National Institute for Occupational Safety and Health (NIOSH), 1993)
In 1992, the Bureau of Mines evaluated mineral resources of the 34,043-hectare Caribou City and 41,943-hectare Stump Creek study areas in southeastern Idaho. No resources were delineated. The areas had been proposed for wilderness. Rocks underlying the study area are part of the Idaho-Wyoming Thrust Belt. At Caribou Mountain they have been intruded by diorite-monzodiorite. Where the intrusive rocks contact calcareous members of the thrust belt, skarn bodies have formed that host metal deposits. Gold, both placer and lode, occurs in the Caribou City area, and salt occurs in the Stump Creek area. Production records show 73.5 kg (2,363 ounces) of placer gold were produced; however, field studies indicate more than 2,000 kg (67,000 ounces) probably were recovered. Minor amounts of lode gold, silver, and copper were recovered from the hard rock mines. Production of salt from the Stump Creek study area in the 1860's was used by emigrants on the Oregon trail and also shipped to various mining districts for use in silver recovery. Oil and gas were drilled for, but all holes are plugged and abandoned. There are no current leases. Examined workings consisted of 25 adits, 3 shafts, 50 prospect pits, and extensive placer workings all in the northern tip of the Caribou City area, Current BLM records show 168 placer and 146 lode claims; 14 claims are patented.